Molecular and Serological Detection of Mycobacterium tuberculosis in Dairy Cattle From Sylhet, Bangladesh - Md. Mukter Hossain; Md. Masudur Rahman; Md. Mahfujur Rahman; Hemayet Hossain; Ruhena Begum; Md. Shahidur Rahman Chowdhury; Md. Rafiqul Islam; Md Bashir Uddin (Veterinary Medicine International)
This study aimed to determine the seroprevalence and molecular detection of Mycobacterium tuberculosis (M. tuberculosis) in dairy cattle using ELISA and PCR techniques. A total of 500 samples (250 blood and 250 milk) were collected from various farms in Sylhet, Bangladesh. The seroprevalence was found to be 5.6% in blood samples, with PCR confirming 1.60% and 2.80% positivity in blood and milk samples, respectively. These findings highlight the zoonotic potential and public health significance of M. tuberculosis in cattle, suggesting a need for integrated One Health surveillance.